Integrasi Aspek Afektif melalui Pembelajaran Bahasa Indonesia Berbasis Teks Muatan Kearifan Lokal untuk Membangun Karakter Siswa Sekolah Dasar Pascapandemi Covid-19 - Nur Samsiyah; Endang Sri Maruti; Ririn Nuryanti (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
Indonesian language learning is the parent of science , so it must be carried out oriented to the formation of language skills and other sciences. The success of learning Indonesian cannot be separated from the role of the teacher in teaching activities in developing students' potential so that their cognitive and affective developments. One of the ways in which language learning is developed is through dignified learning that reflects the existence of cultural values ​​and norms. Values ​​and culture can be taught by integrating affective aspects of Indonesian language learning by utilizing texts containing regional cultures that exist around students. The use of texts containing local wisdom serves tointroduce local culture so that it can be preserved and develop a caring and proud character of ancestral heritage. Various kinds of texts containing local wisdom such as texts on the theme of art, customs, mutual cooperation activities, traditional food and other regional cultures